Echolocation calls of free-flying common vampire bats Desmodus rotundus (Chiroptera: Phyllostomidae) in Chile. Issue 2 (4th May 2017) - Rodríguez-San Pedro, Annia; Allendes, Juan Luis
Abstract: We recorded and characterized the echolocation calls emitted by the common vampire bat Desmodus rotundus during foraging in natural habitats in Chile. Signal design typically shows multiple harmonics consisting of a brief quasi-constant frequency (QCF) component at the beginning of the pulse followed by a downward frequency modulated component. Calls are characterized by long durations (5.5 ms) and emitted as single pulses or in groups of 2–3 pulses at a repetition rate of 29 Hz. The higher frequency ranges (85–35 kHz) and the unusual QCF component that characterized multiharmonic signals of free-flying D. rotundus in Chile is a remarkable feature for acoustic identification with other Chilean bats.